A Simple Approach for Enhancing the Output Performance of Solar-Pumped Solid-State Lasers. (8th February 2009) - Liang, Dawei; Pereira, Rui
Abstract : A simple truncated fused silica elliptical cavity is proposed to enhance the output performance of solar-pumped solid-state lasers. The imaging property of the truncated elliptical cavity ensures an enhanced absorption distribution within an Nd:YAG rod. Optimum pumping parameters are found through ZEMAX nonsequential ray-tracing and LASCAD laser cavity analyses. Compared with the output laser performance of a 3D-compound parabolic concentrator-2D-compound parabolic concentrator (3D-CPC-2D-CPC) cavity, the truncated cavity provides 11% more multimode and 72.7% moreTEM 00 laser powers. A laser beam of high beam quality can be produced efficiently. The standard tracking error for multimode laser power is also reduced to only 4.0% by the truncated cavity.